Theorizing in the qualitative study of mergers & acquisitions - Satu Teerikangas; Helen Colman (Elsevier, 2022)
This paper focuses on theorizing in the study of mergers and acquisitions (M&As), a globally significant inter-organizational phenomenon. We analyze 76 qualitative papers on M&As published in leading management journals between 1966–2016. We identify five modes of theorizing in the study of M&As. We find that M&A scholars make theoretical contributions using different theoretical positioning and research design strategies. The majority of the papers offer a contribution to middle-range theorizing (i.e., the literature on M&As), while a third of the papers also contribute to higher-order, or grand theories in management. In closing, this leads us to call for a rejuvenation of middle-range theorizing in management research.